2000
DOI: 10.1006/viro.2000.0254
|View full text |Cite
|
Sign up to set email alerts
|

Passive Infusion of Immune Serum into Simian Immunodeficiency Virus-Infected Rhesus Macaques Undergoing a Rapid Disease Course Has Minimal Effect on Plasma Viremia

Abstract: Antibody responses are often considered to play only a limited role in controlling viremia during chronic infections with human or simian immunodeficiency virus (SIV). We investigated this by determining the effect of passively infused antibody on plasma viremia in infected rhesus macaques. The emphasis of the study was to understand the mechanism(s) underlying any observed effects. We infused serum immunoglobulins (SIVIG) purified from SIV(mac)251-infected macaques into other SIV(mac)251-infected macaques. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 66 publications
5
29
1
Order By: Relevance
“…Furthermore, correlative studies with humans and direct data from macaques indicate that antibodies may also play a role in controlling viral burden once infection is established (5,13,26).…”
mentioning
confidence: 99%
“…Furthermore, correlative studies with humans and direct data from macaques indicate that antibodies may also play a role in controlling viral burden once infection is established (5,13,26).…”
mentioning
confidence: 99%
“…However, it is unlikely that antibodies play a major role in controlling virus replication in the chronic phase of infection, as demonstrated by passive infusion of immune serum experiments in HIV-1-infected patients 45,46 and SIV-infected macaques. 47,48 Although it can be argued that the mechanism of action of infused antibodies in these studies [45][46][47][48] is inconsistent with virus neutralization, but may be virus mediated, infusion of a combination of the most potent neutralizing antibodies had very little effect on postinfection VL in HIV-1-infected human peripheral blood leukocyte (hu-PBL) severe combined immunodeficient (SCID) mice. 49 Antibody failure to control viral replication is also due to delays in antibody production in the face of a very rapidly evolving virus, such that the swift appearance of escape mutants far outpaces adaptation of the humoral responses to recognize them.…”
Section: Discussionmentioning
confidence: 98%
“…The relative roles of neutralization and Fc-mediated effects in HIV-1 infection have not yet been directly determined. In a recent study, Binley and colleagues (7) suggested that a transient effect on viral load by the infusion of anti-SIV antibodies was likely due to killing of SIV-infected cells, although this conclusion could only be drawn by inference.…”
Section: Discussionmentioning
confidence: 99%
“…The effects on viral load observed were very modest and transient, with kinetics which seemed inconsistent with the neutralization of free viruses as the mechanism driving the effect, and a role of Fc-mediated effector mechanisms was therefore suggested. An experiment using SIVIG F(abЈ) 2 fragments to address this hypothesis, however, was inconclusive (7).…”
mentioning
confidence: 99%